Depend on God: The Overview of Spirituality in Mualaf - Haq, Muhammad Shodikul; Damarhadi, Suprastowo; Arsoniadi, Adi; Prabawanti, Ciptasari; Rosmiani, Rosmiani (Jurnal Ilmiah Psikomuda (JIPM) Connectedness, 2023)
The conversion of religions from non-Islam to Islam is often a moment of spiritual awakening for converts. They feel they have a stronger connection with God and experience a deep feeling of peace and happiness towards their new faith. This study aims to explore in depth the description of spirituality in converts from non-Islamic religions to Islam. The method used in this research is a qualitative phenomenologys approach. Data collection techniques in this research are interviews and observation. The subjects in this research were dua converts who were aged 30-50 years. The research results identified four main themes (Superordinate Themes), namely the power of initial belief, spiritual search, and spiritual experience. The second main theme is the time of religious conversion which consists of sub-themes of decision making, barriers to making a pledge, hiding interest in Islam, recognizing Islamic identity. The third main theme is after converting to Islam which consists of sub-themes of environmental response after religious conversion, social relations after religious conversion, and new spiritual experiences. The last main theme is self-change, which consists of the sub-theme of internalization of the Islamic religion.